Comparison of Growth Performance and Meat Yield of Hilly Chicken under two Feeding Regimens (The Agriculturists, 2013)
A total of 108 day-old chicks of hilly chicken were randomly allocated to either pellet form of high protein-energy diet (PHPE) or mash form of low protein-energy diet (MLPE) dietary group having 3 replications in each group. Birds were reared in cages and studied upto 10 weeks of age to compare their growth, feed efficiency and meat production under two feeding regimens. Six birds from each feeding regimen at the age of 8 week were slaughtered to analyze the meat yield characteristics. The live weight of the birds fed PHPE diet was significantly higher (699±18) than that of MLPE diet (492 ±10) at 8 weeks of age. Feed conversion ratio (FCR) was better in PHPE diet (2.89±0.03) than in MLPE diet (3.22±0.09). The mortality was similar in birds under two different feeding regimens. Live weight (g) and edible parts weight (g) of birds fed on PHPE diet were significantly higher than that of birds fed on MLPE diet. Dressing percentage did not differ significantly between two feeding regimens. It was concluded that native chicken of hilly areas have the potentiality for meat production and they can utilize high protein energy diet more efficiently. DOI: http://dx.doi.org/10.3329/agric.v11i2.17485 The Agriculturists 2013; 11(2) 38-43